DETERMINATION OF THE MAIN DIRECTIONS AND PRINCIPLES OF DEVELOPMENT OF CAD/CAM SYSTEMS IN THE PROCESSING OF WORKPIECES ON CNC MACHINES (Intent Research Scientific Journal, 2023)
Analyses and determinations of the main directions and principles of development of CAD/CAM systems when processing blanks on CNC machines are given in the article.